Criminal of Adverse Pregnant Outcomes: A Perspective From Thyroid Hormone Disturbance Caused by SARS-CoV-2 - Shi, Qiman; Wu, Min; Chen, Pei; Wei, Bo; Tan, Hailong; Huang, Peng; Chang, Shi (Frontiers in Cellular and Infection Microbiology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has caused unprecedented global disturbance. However, limited information has been well demonstrated about the impact on pregnant women with confirmed or suspected coronavirus disease 2019 (COVID-19). Emerging evidence showed adverse pregnant outcomes, including preterm birth, preeclampsia, cesarean and perinatal death occurring in pregnant women after them getting infected by SARS-Cov-2, but the underlying mechanisms remain unveiled. Thyroid hormone is well known for the importance of promoting pregnancy and optimal fetal growth and development. Some studies now indicate that even mild thyroid dysfunction can cause adverse pregnancy outcomes. Furthermore, thyroid dysfunction associated with COVID-19 has been gradually reported. We summarized current knowledge of adverse pregnancy outcomes related to thyroid hormone deficiency caused by coronavirus infection, as well as to accentuate the importance of thyroid hormone surveillance for COVID-19 infected pregnant women.